Addresses on the book of Joshua - Ironside, Henry Allen, 1876-1951 (Neptune, NJ Loizeaux Brothers, 1950)
Includes bibliographical references.
Brethren writer.
Keywords: Bible. O.T. Joshua -- commentaries